(untitled) (Journal of Parents and Teachers, 2021)
COVID-19 has changed in less than a year the educational practice we were used to. In this article we intend to give our vision of the new educational reality from our perspective from student teaching in schools. We intend to reflect all the changes that the pandemic has caused and how schools have managed to cope with them.